2017
DOI: 10.1200/jop.2017.020818
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Introducing Outpatient Specialty Palliative Care in Gynecologic Oncology

Abstract: Gynecologic oncologists have developed strategies for introducing palliative care services to alleviate patient concerns. These strategies provide groundwork for developing system-wide best practice approaches to the presentation of palliative care referral.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…"[I had] a patient that was living at home with her husband and she was falling all the time and was back and forth into the hospi-tal…It was almost to the point where I was [considering] calling Adult Protective Services because the husband really couldn't take care of her… But palliative care wasn't involved in that, and sometimes I think most people consider palliative care for cancer patients or patients in a lot of pain, but I think that palliative care could have been beneficial for this patient." (PCP- 14) Interviewees reported that providers across different settings could help identify palliative care needs for patients by drawing on each provider's unique perspective. That is, participants explained that each provider has access to different cues that palliative care may be needed based on their setting and relationship to the patient.…”
Section: Providers Across Settings Can Identify Palliative Care Needsmentioning
confidence: 99%
See 2 more Smart Citations
“…"[I had] a patient that was living at home with her husband and she was falling all the time and was back and forth into the hospi-tal…It was almost to the point where I was [considering] calling Adult Protective Services because the husband really couldn't take care of her… But palliative care wasn't involved in that, and sometimes I think most people consider palliative care for cancer patients or patients in a lot of pain, but I think that palliative care could have been beneficial for this patient." (PCP- 14) Interviewees reported that providers across different settings could help identify palliative care needs for patients by drawing on each provider's unique perspective. That is, participants explained that each provider has access to different cues that palliative care may be needed based on their setting and relationship to the patient.…”
Section: Providers Across Settings Can Identify Palliative Care Needsmentioning
confidence: 99%
“…13 Additionally, solutions to address these challenges often focus on support for individual or specialist providers, such as oncologists, rather than improving coordination and information sharing across settings and providers. 3,14-16…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gynecological cancers have characteristics of high morbidity, high mortality, and recurrence. 11 , 12 Moreover, rational use of some technical methods to study the spatial distribution of gynecological cancer and identify areas with high incidence of gynecological cancer can help improve the efficiency of early screening. In particular, the late treatment of gynecological cancer is not effective.…”
Section: Introductionmentioning
confidence: 99%
“…3 Disruption of these attachments can lead to negative consequences, such as perceptions of abandonment, 4 which has implications for quality EOL cancer care, including serving as a deterrent to enrollment in palliative care programs, potentially affecting advanced care planning discussions, and causing shock and distress from lack of closure of this valued relationship. [4][5][6][7][8][9][10] Relationships between the patient and HCP may be affected not only by the termination of the relationship but also by negative changes in the relationship near EOL, including rushed visits and poor communication or miscommunication. [10][11][12][13] Stanley 11(p936) has characterized these negative changes as "emotional abandonment."…”
mentioning
confidence: 99%